Resistance analysis of sheep hides ½ Poll Dorset ½ Santa Inês submitted to two tanning techniques (Research, Society and Development, 2022)
This study aimed to analyze the leather resistance of sheep skin ½ Poll Dorset ½ Santa Inês. Twenty hides were distributed in a completely randomized design, in a 2x2x2 factorial, consisting of two tanning techniques (Trat1=with chromium salts. Trat2=without chromium salts), two leather regions (R1=dorsal; R2=ventral) and two-way leather (S1=longitudinal; S2=transversal). In chrome-tanned leathers, the tensile strength (9.48 KgF) was lower (p